2015
DOI: 10.7727/wimj.2014.119
|View full text |Cite
|
Sign up to set email alerts
|

Priapism in Homozygous Sickle Cell Disease: A 40 year Study of the Natural History

Abstract: INTRODUCTIONPriapism, an involuntary and usually painful penile erection, is a major problem in patients with homozygous sickle cell (SS) disease, and is most common in adolescence and early adult life. There are two principal patterns, stuttering episodes and major attacks. Stuttering episodes are predominantly nocturnal, last three to four hours, are relieved by simple physical procedures such as cold showers or exercise, and patients maintain normal erectile function. Major attacks last more than six hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…(6) These episodes are usually underestimated, not only because patients do not seek care out of embarrassment, but also as many of them do not see it is as a result of SCD. (16) In this study, the prevalence of priapism in men with SCD was similar to those found in the literature. (10,16,17) The genetic type HbSS was related to episodes of priapism, which is also in accordance with other series.…”
Section: ❚ Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…(6) These episodes are usually underestimated, not only because patients do not seek care out of embarrassment, but also as many of them do not see it is as a result of SCD. (16) In this study, the prevalence of priapism in men with SCD was similar to those found in the literature. (10,16,17) The genetic type HbSS was related to episodes of priapism, which is also in accordance with other series.…”
Section: ❚ Discussionsupporting
confidence: 89%
“…(16) In this study, the prevalence of priapism in men with SCD was similar to those found in the literature. (10,16,17) The genetic type HbSS was related to episodes of priapism, which is also in accordance with other series. (10,18) Priapism initially manifests itself as minor episodes or PE in childhood and adolescence.…”
Section: ❚ Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Painful involuntary erection of the penis is a common problem among African patients especially in adolescence and early adult life. The prevalence is often underestimated because of embarrassment and the lack of realization that the complication is due to sickle cell disease but direct questioning in adults indicates frequencies of 38-42 per cent 61 62 , and in the Jamaican Cohort where direct questioning was routine, the cumulative incidence rose to nearly 60 per cent in those surviving to the age of 40 yr 63 (Serjeant & Hambleton - unpublished data). In Indian patients, this complication may occur 64 but appears to be rare.…”
Section: Priapismmentioning
confidence: 99%
“…SCD interferes in man's life, delays sexual maturation, compromises physical development and causes limitations in several levels due to the clinical variability of this disease 4 . Priapism is among the SCD complications and retrospective data points out that it affects approximately 30% of men with SCD 5 . SCD causes ischemic priapism, with time-dependent hypoxia, hypercapnia, and acidosis.…”
Section: Introductionmentioning
confidence: 99%